2010
DOI: 10.1590/s0006-87052010000300004
|View full text |Cite
|
Sign up to set email alerts
|

Potencial de genótipos de trigo duro para produtividade e caracteres agronômicos no Estado de São Paulo

Abstract: RESUMOO trigo duro produz a semolina que, extraída dos grãos, é a matéria-prima empregada na elaboração de macarrão. Assim, o objetivo deste estudo foi avaliar o potencial produtivo e comportamento agronômico de 17 linhagens de trigo duro (BH-1146 , altura das plantas, comprimento da espiga e comprimento do internódio da raque (cm), número de grãos por espiga e massa de cem grãos (g). A tolerância à toxicidade de alumínio foi realizada empregando soluções nutritivas, no laboratório. As cultivares IAC-1001 e IA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Spike size is an important agronomic trait for breeding, especially as it is positively associated with grain yield. Results from a previous study have shown that a larger spike resulted in a greater number of spikelets (Silva et al, 2010).…”
Section: Discussionmentioning
confidence: 89%
“…Spike size is an important agronomic trait for breeding, especially as it is positively associated with grain yield. Results from a previous study have shown that a larger spike resulted in a greater number of spikelets (Silva et al, 2010).…”
Section: Discussionmentioning
confidence: 89%
“…Table 3: Estimates of phenotypic (r p ), genotypic (r g ) and environmental (r e ) correlation between agronomic traits, for days of emergence to flowering (DF), plant height (PH), spike length (SL), number of tillers (NT), number of spikelets (NS), kernel weight (KW), thousand kernel weight (TK) for wheat genotypes Spike length showed a significant negative genotypic association with thousand kernel weight (-0.442), indicating that larger spikes tend to increase yield. In this way, these traits are important to be considered in the cereals breeding, due to being closely related to the yield components and define wheat productivity (Silva et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the increase in the length of the spike and the mass of grains in the main spike tends to increase the yield of wheat grains. Silva (2009) considers that the spike length is a trait of interest for genetic improvement, as it is closely related to the components that define grain yield in wheat culture.…”
Section: Resultsmentioning
confidence: 99%